Synthesis and Characterization of Psyllium Husk Grafted Copolymers for the Application as Bio- Adsorbent of Heavy Metals - Haque, A K M Abirul; Sayeed, Kazi Araf; Hossain, Md Iqbal (Chemical Engineering Research Bulletin, 2023)
Heavy metal contamination in the environment and food chain is one of the largest concerns of the twenty-first century and a plant derived adsorbent might provide a sustainable solution to this problem. Psyllium Husk (Isobgul) is already consumed as a natural remedy for the treatment of constipation and other health purposes. The objective of the present study was to modify the surface morphology of Psyllium Husk and its use for the adsorption of heavy metals from aqueous solutions. A binary grafted co-polymer of Psyllium mucilage was successfully synthesized by grafting Acrylic Acid and Acrylonitrile monomers onto the polysaccharide chain under microwave irradiation. FTIR spectroscopy confirmed the formation of different functional groups on the polysaccharide chain. SEM analysis showed increased roughness in surface morphology on modified Psyllium Husk. Batch adsorption tests were conducted using this grafted polymer to analyze its adsorption efficiency of Pb (II), Cr (III) and Cd (II) ion. Atomic Absorption Spectroscopy confirmed up to 79% removal of the Lead (II) ion, 42% removal of Cadmium (II) and 45% removal of Chromium (III) ion from aqueous solutions using 0.1 g of adsorbent in 50 ml solution. The adsorption mechanism was studied by fitting the batch adsorption data against various known isotherms and kinetic models. Results showed that experimental data had a better fit against the Langmuir isotherm for Cd adsorption and against the Freundlich isotherm for Pb and Cr adsorption. The time-dependent lead adsorption data were fitted against the pseudo-first order and pseudo second-order model. R2 values (0.7746 for pseudo first-order and 0.9979 for pseudo second-order) show that the adsorption mechanism closely followed the pseudo secondorder model. The results of this study indicate that the grafting capabilities of Psyllium Husk can be leveraged to create Psyllium Husk-based adsorbent in raw water treatment and may have further applications as dietary supplement that can effectively remove heavy metals from the human body provided that this product does not have any level of toxicity for oral consumption. Chemical Engineering Research Bulletin: 23 (Special): 1-5